Neonatal resuscitation practices in Italy: a survey of the Italian Society of Neonatology (SIN) and the Union of European Neonatal and Perinatal Societies (UENPS) - Camilla Gizzi; Daniele Trevisanuto; Luigi Gagliardi; Giulia Vertecchi; Stefano Ghirardello; Sandra Di Fabio; Corrado Moretti; Fabio Mosca (BMC, 2022)
Abstract Background Providing appropriate care at birth remains a crucial strategy for reducing neonatal mortality and morbidity. We aimed to evaluate the consistency of practice and the adherence to the international guidelines on neonatal resuscitation in level-I and level-II Italian birth hospitals. Methods This was a cross-sectional electronic survey. A 91-item questionnaire focusing on current delivery room practices in neonatal resuscitation was sent to the directors of 418 Italian neonatal facilities. Results The response rate was 61.7% (258/418), comprising 95.6% (110/115) from level-II and 49.0% (148/303) from level-I centres. In 2018, approximately 300,000 births occurred at the participating hospitals, with a median of 1664 births/centre in level-II and 737 births/centre in level-I hospitals. Participating level-II hospitals provided nasal-CPAP and/or high-flow nasal cannulae (100%), mechanical ventilation (99.1%), HFOV (71.0%), inhaled nitric oxide (80.0%), therapeutic hypothermia (76.4%), and extracorporeal membrane oxygenation ECMO (8.2%). Nasal-CPAP and/or high-flow nasal cannulae and mechanical ventilation were available in 77.7 and 21.6% of the level-I centres, respectively. Multidisciplinary antenatal counselling was routinely offered to parents at 90.0% (90) of level-II hospitals, and 57.4% (85) of level-I hospitals (p < 0.001). Laryngeal masks were available in more than 90% of participating hospitals while an end-tidal CO2 detector was available in only 20%. Significant differences between level-II and level-I centres were found in the composition of resuscitation teams for high-risk deliveries, team briefings before resuscitation, providers qualified with full resuscitation skills, self-confidence, and use of sodium bicarbonate. Conclusions This survey provides insight into neonatal resuscitation practices in a large sample of Italian hospitals. Overall, adherence to international guidelines on neonatal resuscitation was high, but differences in practice between the participating centres and the guidelines exist. Clinicians and stakeholders should consider this information when allocating resources and planning perinatal programs in Italy.